Yemeni EFL Student Teachers’ Moral Intelligence and its Relationship to their Academic Achievement - Al-Mekhlafi, Mohammad Abdu Ahmed (Journal of Humanities & Social Sciences, 2020)
This corelational study aimed at investigating the relationship between the moral intelligence of a group of Yemeni EFL student teachers and their academic achievement. It also aimed at finding out any statistically significant differences between the moral intelligence of the student teachers who are categorized into high and low achievers. One hundred and twelve Yemeni EFL student teachers of a third level in the teacher preparation program at the Department of English in the College of Education at Sana’a University in Yemen participated in this study. Their ages ranged between 21 and 25 years. Data were collected using a literature-based questionnaire. The results of this study show that the mean of the ten categories of the moral intelligence is 4.02 (80.4%) indicating a high degree of moral intelligence. The results show that there is no statistically significant differencesat the 0.05 level between the moral intelligence and academic achievement in the Morphology and Syntax course. The results also indicate that there are no statistically significant differences at the level of 0.05 between high and low achievers on nine categories of the moral intelligence. Furthermore, the results indicate that there are no statistically significant differences at the level of 0.05 between female and male student teachers on nine categories of the moral intelligence, namely: Faith, Honesty, Integrity, Courage, Discipline, Responsibility, Service, Kindness and Courtesy. The study findings confirm the previous studies and present some suggestions for further research.
Keywords: moral intelligence; academic achievement; student teachers; Yemen